Pregnancy Massage Pada Ibu Hamil Trimester III Dengan Nyeri Akut - Jaya, Herawati; Ningsih, Ratna; Marcelah, Putri Bella (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background : The pregnancy period is a time when pregnant women experience physical and psychological changes so that pregnant women have to experience a lot of discomfort. Pregnancy is a special period in life that is associated with hormonal and physiological changes in pregnant women, which can cause or change the course of neurological and psychiatric disorders. In the third trimester, one of the discomforts that often occurs is back pain. During pregnancy, back pain is a problem that often occurs, especially in the last three months of pregnancy. At this gestational age, pregnant women often appear worried, perhaps feeling pain in the third trimester. Method : This case study design uses a descriptive research design in the form of a case study. This research data was taken through interviews, observation, examination, implementation and pain assessment scales. The case study subjects were 3 people 3-4 hours in the third trimester with acute pain problems at the Muhammadiyah Palembang Hospital, in March and April 2024. Results : Nursing care with the implementation of pregnancy massage nursing showed a reduction in pain levels from a moderate pain scale to a mild pain scale in the three patients. Conclusion : The implementation of pregnancy massage nursing showed the effectiveness of reducing pain levels in patient.